Kinetics of Neutrophil Subsets in Acute, Subacute, and Chronic Inflammation - Bongers, Suzanne H.; Chen, Na; van Grinsven, Erinke; van Staveren, Selma; Hassani, Marwan; Spijkerman, Roy; Hesselink, Lilian; Lo Tam Loi, Adèle T.; van Aalst, Corneli; Leijte, Guus P.; Kox, Matthijs; Pickkers, Peter; et al. (Frontiers in Immunology, 2021)
The vast majority of neutrophils in the circulation expresses CD16 and CD62L in homeostasis within a narrow expression range, but this quickly changes in disease. Little is known regarding the changes in kinetics of neutrophils phenotypes in inflammatory conditions. During acute inflammation more heterogeneity was found that was characterized by an increase in CD16dim banded neutrophils. These cells were probably released from the bone marrow (left shift). Acute inflammation induced by human experimental endotoxemia (LPS model) was additionally accompanied by an immediate increase in a CD62Llow neutrophil population, which was not as explicit after injury/trauma induced acute inflammation. The situation in sub-acute inflammation was more complex. CD62Llow neutrophils appeared in the peripheral blood several days (>3 days) after trauma with a peak after 10 days. A similar situation was found in the blood of COVID-19 patients returning from the ICU. Sorted CD16low and CD62Llow subsets from trauma and COVID-19 patients displayed the same nuclear characteristics as found after experimental endotoxemia. In diseases associated with chronic inflammation (stable COPD and treatment naive HIV) no CD16low or CD62Llow neutrophils were found in the peripheral blood. All neutrophil subsets were present in the bone marrow during homeostasis. After LPS rechallenge, these subsets failed to appear in the circulation, but continued to be present in the bone marrow, suggesting the absence of recruitment signals. Because the subsets were reported to have different functionalities, these results on the kinetics of neutrophil subsets in a range of inflammatory conditions contribute to our understanding on the role of neutrophils in health and disease.